Deputation to the Minister of Health - National Anti-Vaccination League (Great Britain) (London : National Anti-Vaccination League)
1929 1920s 12 pages their opinion and are afraid to look the matter straight in the face." The "Observer" recently reported that two deaths from inflammation of the brain following vaccination had occurred in Denmark, where a Committee of official doctors is sitting to investigate the lymph used in that country. The official statistics do not represent all the cases that have occurred. The Rolleston Committee themselves admit that the information obtained cannot be regarded as being an index of the real prevalence of the condition. But even the Committee's partial figures show that for children under 15 years of age, the risk of death from postvaccinal encephalitis is greater than the risk of death from smallpox. The Committee's post-vaccinal encephalitis cases relate to 58 months of the years 1922-1927, while there were 72 months in those years. The encephalitis deaths in the 58 months numbered 42. For the 72 months of the period there were 45 deaths registered from smallpox in children under 15 years, and probably some of these were not from smallpox at all. Encephalitis after vaccination killed 42 children in 58 months ; smallpox, at the very most, killed 45 children in 72 months. Dr. Percy Rose, in a letter to the "British Medical Journal" for 8th June, 1929, warns his fellow practitioners of the risk of postvaccinal encephalitis when vaccinating children of school age. We can well believe that ever since this terrible danger began to be prominent, every effort has been made by the Government Lymph Establishment to issue lymph that will not give rise to this complication. As cases continue to occur, such efforts must have been fruitless. "The Medical Officer" for 6th July, 1929, states that the essence of what is known of post-vaccinal encephalitis is condensed in the paragraph from the report of the Session Ordinaire d'Octobre, 1928, du Comite de l'Office International d'Hygiene publique, which they have translated as follows. (I give the part to which I wish to call your attention) :— "Post-vaccinal encephalitis continues to occur in Holland. In the first six months of 1928 its incidence was the same as in 1927 namely, one case per 2,800 vaccinations." "The Medical Officer" comments as follows :— "The incidence of one case per 2,800 vaccinations is far higher than the records of this country suggest, but the precise incidence, the actual measure of the risk, is not known. At least three undoubted cases of the disease have been investigated by coroners in London recently ; but we do not know whether these are all that have occurred, or how many vaccinations have been performed amongst those to whom encephalitis is a risk." It must be borne in mind, however, that even if the risk of encephalitis after vaccination could be eliminated, there are still other risks from the use of a living virus. During the 24 years ending December, 1928, only 88 children under five died from smallpox, while 232 died from cowpox and other effects of vaccination, according to the Registrar-General's returns and replies to questions in Parliament. Bronchitis, pneumonia, generalised vaccinia, asthenia, enteritis, convulsions, meningitis, pemphigus, erysipelas, septicaemia, cellulitis, marasmus, toxaemia, gangrene of the arm—these are some of the causes of death, in the deaths returned as "vaccinia" deaths, in the Registrar-General's Statistical Review, 1911-1925 (pages 221-223 of the Rolleston Report.) We have with us this morning the father of one of the latest victims of vaccination, Mr. Smith, father of Vera Smith, aged 14 years, into whose death from vaccination an inquiry was held recently. Mr. Smith can tell you how he was told that his daughter could not return to school unless she was vaccinated. The school authorities were advised by the local Medical Officer of Health to take this course, and the local Medical Officers of Health take their instructions in these matters from officials of your Department. It is your Department that is responsible for these "constructive murders" as Dr. Jameson put it in The "Lancet" last year. You have to remember that the calculations of your officials showing only one death from encephalitis in so many thousand vaccinations do not disclose anything like the whole truth. Doctors and coroners conspire to "save vaccination from reproach." Moreover, a parent of one of the victims of vaccination does not care how few the deaths are if his own loved child is one of them. Would anyone in this room have another child vaccinated, whatever the penalty, after having lost one from the operation? Can we not make you realise what these parents are feeling? Will you not understand that it is your Department that is causing all this suffering and sorrow? This morning yet another death from vaccination is being inquired into at Stepney. Very mild smallpox, perhaps not smallpox at all, was made the excuse for vaccinating a child of five who had just recovered from a severe illness. Her parents were frightened by the bogy of smallpox, and consented to the operation. In a fortnight the child was dead — dying, as so many of these cases have died, after a few hours of unconsciousness. Even if vaccination protected from smallpox, which it does not, these deaths from the operation would justify you in repealing 36/H24/24